Role of Nonlinear Processes in Instability of Dynamical Systems in Economics Applications - Zhokhin, A.S. (Ukrainian Journal of Physics, 2022)
We study the influence of an external investment on the stability of equilibrium prices in an economic system which is described by the equations of evolution of prices of goods with regard for the balance of supply and demand, as well as the external investment in the economic system. It is shown that sufficiently high levels of investments lead to the loss of stability of the equilibrium state.